(untitled) (Ecological Bulletin of Kryvyi Rih District, 2025)
This article presents the results of in vitro propagation of Ptelea trifoliata L. from the collection at Tashkent Botanical Garden. In vitro propagation plays a key role in conserving threatened plant species, as many species face increasing extinction risks due to environmental changes and human activities. To address this, the Biotechnology Laboratory at the Institute of Botany in Tashkent has initiated a program focused on the in vitro preservation of plant species, including those at risk of extinction. The collection includes both plants from natural habitats and specimens maintained within the Botanical Garden. Several culture media were tested for their effectiveness in supporting the in vitro propagation of Ptelea trifoliata. Among the options evaluated, McCown’s Woody Plant Medium (WPM) with additional vitamins from Duchefa Biochemie B.V. was identified as the most suitable for this species. WPM, specifically designed for woody plants, provided an optimal nutrient composition that promoted healthy growth and development of the plant material. This medium was further enriched with plant growth regulators, including indole-3-butyric acid (IBA), 1-naphthaleneacetic acid (NAA), and 6-benzylaminopurine (BAP), to stimulate optimal root and shoot development. In conclusion, this study demonstrates the successful in vitro propagation of Ptelea trifoliata using McCown’s Woody Plant Medium supplemented with IBA, NAA, and BAP. The refined protocol enhances explant viability and facilitates the large-scale propagation of this species, making it a valuable tool for conservation and large-scale propagation initiatives. Through tissue culture techniques, this approach offers a sustainable solution to preserve plant biodiversity, ensuring that endangered species are protected for future generations.